SOSIALISASI PERAN APOTEKER DALAM MENCEGAH PENGGUNAAN KOSMETIK ILEGAL PADA SISWA/SISWI KELAS XI SMKS TUNAS HUSADA KENDARI - Hasnawati Hasnawati; Rifa’atul Mahmudah; Nur Azizah; Zabrina D. Masjidi; Umi Hasana; Crisna Welliam; Kharisma Restu Al Hijrah Ode (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
The use of cosmetics among adolescents is increasing due to beauty trends and easy access to cosmetic products. However, low awareness in identifying safe and legal cosmetics raises the risk of exposure to products that do not comply with safety standards. This community service program aimed to improve the knowledge and awareness of students at SMK Tunas Husada Kendari regarding the identification and selection of safe and legal cosmetics through interactive education. The activities included counseling sessions, group discussions, Q&A, and evaluation using pre-test and post-test questionnaires. The results showed a significant increase in students’ understanding after the intervention. Participants were able to recognize the characteristics of safe cosmetics, verify product legality using BPOM registration numbers via the BPOM Mobile application, and understand the health risks of illegal cosmetics such as mercury, hydroquinone, and steroids. In conclusion, interactive educational methods proved effective in enhancing students’ knowledge and encouraging them to become smart consumers who prioritize skin health and product safety.